Pembuatan Methyle Ester Dari Bahan Dasar Asam Lemak - Yemirta Yemirta (Balai Besar Kimia dan Kemasan, 1997)
Methyl Ester is produced by esterification of fatty acid and methanol using sulfuric acid as a catalyst. In this research methyl laurate was made from lauric acid and methanol. The ester is extracted with dietil eter and an addition of MgS04 to reduce water. The characteristic of methyl laurate are water-white liquid, insoluble in water, non corrosive and low toxicity.Methyl laurate is used in intermediate for detergents, emulsifiers, wetting agents, stabilizers, lubricants, platicizers, textiles and flavoring.